Optimization of Friction Stir Spot Welding Parameters of Al6061T6 by Hybrid Approached - Mohammed Hussein, Rasha; Fareed Hasan, Sameh; M. Takhakh, Ayad; Abdullah Al-Shammari, Mohsin (Al-Nahrain Journal for Engineering Sciences, 2023)
The most important way for joining the non-welding aluminum alloy is Friction stir spot welding. Three parameters effect on efficiency of welding: tool shape, rotational speed, and plunged time, are chosen to study for welding 6061T6 aluminum alloy. Each of the above parameters has three variables as: pin shapes (square, cylinder, and hexagonal), plunged time (50, 70,100) sec and rotational speeds (710, 1120, 1800) rpm hybrid approach which is consist of the experiment run, neural network and social spider optimization is used to optimize the welding conditions by finding the maximum ultimate force. The best condition of the weldments is (square, 710rpm, 100sec) with maximum shear force 4740N. The best results obtained from hybrid optimization with experimental results; with discrepancy of 2%.